The New Methodology for Assessing of the Applicability of Elastomeric Materials in the Vibration Isolation Systems of Railway Lines - Jarosław BEDNARZ (Archives of Acoustics)
The technical requirements for the determination of physical parameters of vibration isolating material have not been standardized in Europe and Poland yet, which significantly hinders the ability to compare vibration isolating materials offered on the market. Therefore, there is a need for establishing a norm that could be applied both for the determination of the physico-mechanical properties of elastic vibration isolation elements in rail transport for domestic and foreign producers as well as in their selection for application in a specific vibration isolation system. The paper presents a proposal to standardize the methodology of the estimation of vibration isolation materials physical parameters authorized for use in vibration isolation systems used in rail transport. Methodology for measuring the physico-mechanical parameters of vibration isolating material presented in the paper forms uniform test procedure developed based on a fragmentary norms for flexible materials testing. The use of the proposed research methodology enables the creation of a unified database of elastic materials which parameters will be easy to compare, and choice between them will become easier for designers of vibration isolation systems used in rail transport.